MOTIF DALAM PENYELENGGARAAN PENDIDIKAN ISLAM DAN IMPLIKASINYA TERHADAP POLA KEPEMIMPINAN DAN MANAJEMEN - Mahmud, Eka (Universitas Nurul Jadid, 2014)
The spirit of establishing Islamic educational institutions looks so great despite has variety of motives. Similarly, most people who wish to provide studying about Islam to the sons and daughters of Islamic educational institutions are being intensified. Therefore, one of the motives in Islamic education is to meet their educational needs, in addition to other motives. The motive will certainly have implications for the survival of the institution. For educational institutions that purely have the anxiety motive for Community’s education performance might be more lasting than those are motivated by economic investment because it applies the concept of community-based education (community based education)